A systematic review and meta‐analysis of clinical predictors of lithium response in bipolar disorder. (30th June 2019) - Hui, T. P.; Kandola, A.; Shen, L.; Lewis, G.; Osborn, D. P. J.; Geddes, J. R.; Hayes, J. F.
Abstract : Objective: To determine clinical predictors of lithium response in bipolar disorder. Methods: Systematic review of studies examining clinical predictors of lithium response was conducted. Meta‐analyses were performed when ≥2 studies examined the same potential predictor. Results: A total of 71 studies, including over 12 000 patients, identified six predictors of good response: mania‐depression‐interval sequence [odds ratio (OR): 4.27; 95% CI: 2.61, 6.97; P < 0.001], absence of rapid cycling (OR for rapid cycling: 0.30; 95% CI: 0.17, 0.53; P < 0.001), absence of psychotic symptoms (OR for psychotic symptoms: 0.52; 95% CI: 0.34, 0.79; P = 0.002), family history of bipolar disorder (OR: 1.61; 95% CI: 1.03, 2.52; P = 0.036), shorter prelithium illness duration [standardised mean difference (SMD): −0.26; 95% CI: −0.41, −0.12; P < 0.001] and later age of onset (SMD: 0.17; 95% CI: 0.02, 0.36; P = 0.029). Additionally, higher body mass index was associated with poor response in two studies (SMD: −0.61; 95% CI: −0.90, −0.32; P < 0.001). There was weak evidence for number of episodes prior to lithium treatment (SMD: −0.42; 95% CI: −0.84, −0.01; P = 0.046), number of hospitalisations before lithium (SMD: −0.40; 95% CI: −0.81, 0.01; P = 0.055) and family history of lithium response (OR: 10.28; 95% CI: 0.66, 161.26; P = 0.097). Conclusions: The relative importance of these clinical characteristics should be interpreted with caution because of potential biases and confounding.